The role of nurses in ostomy care - Medeiros, Anna Carolina Lomelino Lemos (2021)
Introduction: When mentioning the word “ostomy”, it is understood as a surgical procedure performed to exteriorize part of a system, whether respiratory, urinary or even digestive. Stoma is the formation of a new opening artificially, allowing communication between the internal and external environment. Objective: To identify the role of nurses during the care of ostomized patients. Methodology: An integrative review was carried out and as a tactic for identification and selection of documents, the search was carried out by searching the Virtual Health Library (VHL) during the month of April 2021. Materials that had the following in their summary were sought. descriptors in health sciences (DeCS) Nurse; Nursing care; Ostomy. Results: From the thorough reading of the articles, two categories were developed. Category I- Difficulties encountered by professional nurses in caring for ostomized patients; Category II- The importance of nursing in promoting self-care for ostomized individuals. Final Considerations: that nursing care is essential for ostomized individuals and that even with the technical processes based on scientific conceptions carried out by the professional nurse, it is essential to establish a bond with their clients, taking into account their ethical, moral, religious issues and their unique personalities , making individual care.